EVALUASI USABILITY APLIKASI SIKAWAN DINAS PARIWISATA KABUPATEN LINGGA MENGGUNAKAN SYSTEM USABILITY SCALE - Diorsa Yamagi (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Digital transformation in government administration has driven the development of various e-government platforms aimed at improving the quality of public services. The Tourism Department of Lingga Regency developed the Tourist Visit Information System (SIKAWAN) as an integrated digital platform managing information on accommodations, tourist attractions, MSME products, and tour guides. As the application remains in a beta-testing phase and has not been officially launched, an evaluation of its usability is critically needed prior to public release. This study aims to evaluate the usability level of the SIKAWAN application using the System Usability Scale (SUS) method. A descriptive quantitative approach was adopted with 23 respondents from the Lingga Regency Tourism Department who had used the application during the testing phase, selected through purposive sampling. Data were collected online via Google Form in May 2026. The evaluation results show an average SUS score of 58.26, placing SIKAWAN in the "OK" category with a "Marginal Low" level of acceptability based on the Bangor et al. (2009) classification. These findings indicate that the SIKAWAN application is functional but has not yet reached optimal usability standards, requiring improvements in the data input flow for tourist attractions, interface consistency, and content enrichment before its official public release.Keywords: E-Government, Usability, System Usability Scale, SIKAWAN, Digital Tourism.